Role of endothelin 1 in steroid production by ovine granulosal cells collected from large preovulatory follicles - Perea Ganchou, Fernando; Keith Inskeep, Emmett; Flores, Jorge Antonio (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
For this experiment it was hypothesized that endothelin 1 (END1) acting through its receptors, endothelin receptor type A (ENDRA) and/or endothelin receptor type B (ENDRB), on granulosal cells (GC) of ovine preovulatory follicles would inhibit steroid production, and therefore, prevent the premature luteinization of granulosal cells of those follicles. The ovaries of 17 Suffolk ewes were removed by mid-ventral laparotomy after two doses of PGF2a (5 mg; three h apart). Granulosal cell were harvested under sterile conditions from the two or three largest follicles. Aliquots of 15 µL of GC suspension from each presumed preovulatory follicle were cultured in 96-well plates containing a solution of 185 µL of Ham´s F12 supplemented medium and treatments (single and combined effects of LH, END1, ENDRA and ENDRB). According to estradiol (E2) concentration in follicular fluid (FF), presumed preovulatory follicles were categorized in estrogen-active and estrogen-inactive follicles. Data from 20 estrogen-active follicles (collected from 13 ewes) challenged to 10 different treatments were examined by analysis of variance. Accumulation of E2 and progesterone (P4) by cultured GC was not affected by either LH or END1 or the END receptor blockers. Granulosal cells from follicles with the greatest concentration of E2 in FF produced on the average significantly more E2 and P4 than follicles with lower concentrations of E2 in FF (P < 0,0001). In conclusion, under the experimental conditions of this study, END1 did not affect steroid production by GC from preovulatory follicles in sheep, and therefore the working hypothesis was not supported.